USING CARDIO TRAINING TOOLS TO IMPROVE THE PHYSICAL CONDITION OF 14-15 YEAR OLD ATHLETES (Physical Culture and Sport: Scientific Perspective, 2025)
The scientific work has analyzed domestic and foreign literary and Internet sources on the selected research issues, which allowed to substantiate the relevance of the study. In the study, thanks to the theoretical processing of the data, it was possible to provide a detailed description of the system for planning the educational and training process of young athletes aged 14-15. The work describes the current features of the use of running training equipment in the training of athletes.It was possible to determine the most relevant methods of training young athletes and characterize the features of the use of various cardio training equipment for athletes aged 14-15. Methodological aspects for the implementation and dosage of cardio training equipment at different stages of long-term improvement (detailed at the stage of specialized basic training) of athletes are described. The features of the use of general and special (speed, coordination and strength) endurance tools as the main ones for track and field athletes and other athletes at various stages of long-term improvement have been studied and characterized.Optimization of the tools and methods of using cardio exercises and their appropriate use will contribute to achieving the expected results, namely, increasing oxygen consumption and aerobic performance, increasing the level of general endurance and individual indicators of special endurance. Particularly relevant when using cardio training are indicators of reducing the risk of overloading athletes and attracting more children to athletics.Key cardio training tools have been substantiated to improve the general physical condition of track and field athletes 14-15 years old at the stage of specialized basic training. Cardio training tools are also especially necessary to improve the physical condition of young track and field athletes 14-15 years old at the stage of preliminary basic training.According to the results of the research and the generalization of the data, it was possible to determine the means of cardio training for young athletes: running at different speeds (steady, alternating, cross-country), game-oriented exercises (relays, outdoor games), which significantly diversify the training process, simulators with cyclic dynamics of movements, as an alternative to running to reduce the impact load, types of swimming exercises, as a universal means of developing endurance and recovery, running with a change in speed, which is relevant for children 14015 years old in moderate volumes. Only thanks to optimally and rationally dosed cardio loads can high expected results be achieved: increasing the level of oxygen consumption, aerobic performance, improving the level of general endurance and speed-strength readiness, reducing the likelihood of overloads and injuries during training, involving children in athletics for children aged 14-15 years.
Keywords: athletics; cardio training; preparation period; general and special endurance